Bystander T-Cells Support Clonal T-Cell Activation by Controlling the Release of Dendritic Cell-Derived Immune-Stimulatory Extracellular Vesicles - Lindenbergh, Marthe F. S.; Koerhuis, Daniëlle G. J.; Borg, Ellen G. F.; van ‘t Veld, Esther M.; Driedonks, Tom A. P.; Wubbolts, Richard; Stoorvogel, Willem; Boes, Marianne (Frontiers in Immunology, 2019)
Extracellular vesicles (EV) that are released by immune cells are studied intensively for their functions in immune regulation and are scrutinized for their potential in human immunotherapy, for example against cancer. In our search for signals that stimulate the release of functional EV by dendritic cells we observed that LPS-activated human monocyte-derived dendritic cells (moDC) changed their morphological characteristics upon contact with non-cognate activated bystander T-cells, while non-activated bystander T-cells had no effect. Exposure to activated bystander T-cells also stimulated the release of EV-associated proteins by moDC, particularly CD63 and ICAM-1, although the extent of stimulation varied between individual donors. Stimulation of moDC with activated bystander T-cells also increased the release of EV-associated miR155, which is a known central modulator of T-cell responses. Functionally, we observed that EV from moDC that were licenced by activated bystander T-cells exhibited a capacity for antigen-specific T-cell activation. Taken together, these results suggest that non-cognate interactions between DC and bystander T-cells modulates third party antigen-specific T-cell responses via EV.